Young children's views on play provision in two local parks: A research project by early childhood studies students and staff. (November 2019) - Yates, Ellen; Oates, Ruby
This project collected the views of young children on play provision within two local parks through research conducted by Early Childhood Studies students and academics. Findings identified that traditional playground equipment and 'risky' play were important for children. Natural features and semi-permanent provision were valued, alongside the provision of mixed-age fixed equipment. Children were highly aware of health and safety, and they were very risk averse. Conclusions recognised constraints and limitations of collaborative working, including eliciting authentic voices of children.